Does IT innovation asset lead to businness innovations: IT business innovation capability lens - Badewi, Amgad; Essam, Shehab (British Academy of Management, 2014)
The aim of this research is to understand the factors that affect the ability of an organization to innovate, using information technologies, in its business – including products, processes, and business models. IT business innovation (ITBI) assets, i.e. integration; data analysis; and social media technologies, are proposed to have an impact on business innovation. Since IT in itself is not a source of value without a proper organizational capability to absorb its capacity, IT business innovation capability is proposed as a robust concept between the impact of IT innovation assets and business innovation. Business innovation capabilities are proposed to be generating valid ideas (interpretive, critical, and positive competences) and idea implementation (innovation sponsorship and organizational flexibility competences) capabilities.
Keywords: IT business innovation; organization flexibility; capability theory; exploratory competences; exploitative competences; Knowledge Creation theory